The endcap disc DIRC for PANDA at FAIR - Schmidt, M.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; et al. (Nuovo Cimento Della Societa Italiana Di Fisica C, 2019)
The Endcap Disc DIRC for the PANDA experiment is going to provide an excellent particle identification up to particle momenta of 4GeV/c. It covers the polar angles from 5° to 22° and guarantees a separation power of more than 3 standard deviations (s.d.) for pions and kaons in the required phase space. The simulated detector performance has been validated during several testbeam campaigns. Additionally, the transmission losses of the optical filter has been investigated to estimate the filter performance at the end of the PANDA lifetime.
CRIS-Team Scopus Importer:2019-07-19